Dual-affinity peptide mediated inter-protein recognition. Issue 48 (24th November 2016) - Duan, Hongyang; Zhu, Ling; Hou, Jingfei; Peng, Jiaxi; Xie, Hanyi; Lin, Yuchen; Liu, Changliang; Li, Wenzhe; Xu, Haiyan; Wang, Chen; Yang, Yanlian
Abstract : A dual-affinity peptide E5 mediated enhanced interaction affinity between human serum albumin (HSA) and a membrane protein (chemokine receptor CXCR4). Abstract : We present for the first time an enhanced interaction affinity between an abundant soluble protein (human serum albumin) and a membrane protein (chemokine receptor 4) mediated by a dual-affinity peptide E5.